UPAYA MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PENDIDIKAN PANCASILA MELALUI PEMBELAJARAN BERDIFERENSIASI DAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAMS GAMES TOURNAMENT) DI KELAS 5.A SD NEGERI 27 PALEMBANG - Erina Kiranti; Fatia Anta Riska; Febriyani Eka Saputri; Eli Oktaviani; Eko Satria S; Esti Susiloningsih; Febriansyah Farma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to enhance the motivation and learning outcomes of 5.A grade students at SD Negeri 27 Palembang on the topic of Pancasila as a Value of Life through a differentiated learning approach and the cooperative learning model TGT (Teams Games Tournament). The issue addressed is the low motivation and learning outcomes of students. This classroom action research was conducted over three cycles, with each cycle designed to improve student engagement. The results showed significant improvement: cycle 1 reached 51.5%, cycle 2 increased to 66.5%, and cycle 3 achieved 87.5%. This increase in learning outcomes demonstrates that the applied approach is effective in enhancing student motivation and learning results. The improvements observed in each cycle confirm that the differentiated learning approach combined with the TGT (teams games tournament) model can elevate students' learning outcomes. Keywords: Differentiation Learning, Teams Games Tournament, Pendidikan Pancasila